Representasi Lingkungan Alam Kalimantan Melalui Makanan Tradisional Banjar dalam Kisdap Guru Hanyar Karya Hatmiati Mas’ud - Noor Leha (STIKes Ibnu Sina Ajibarang, 2025)
South Kalimantan has a natural environment with abundant natural resource potential. Disclosure of the reality of Banjar people's lives in the social and natural environment is depicted through literary works. Most of the natural resources in the Kalimantan region are used to prepare traditional food for the Banjar people. This research aims to represent the natural environment through the traditional food of the Banjar people. This research method is descriptive qualitative with Garrard's literary ecological approach. The data source for this research is the Kisdap Guru Hanyar by Hatmiati Mas'ud which is contained in Pilanggur: Salusin Kisdap Banjar. The data for this research are words, phrases, dialogues, sentences or interviews that allude to traditional Banjar food to represent the natural environment of Kalimantan. The results of this research reveal 1) the residence shows a strategic location for growing various types of plants as ingredients for processed food or traditional Banjar dishes such as gangan (vegetables), 2) animals including various types of fish that live in Kalimantan waters are used as a staple food source Banjar people mainly use side dishes. The various types of fish that are easy to find also represent the aquatic environment of Kalimantan.